SOCIO-CULTURAL FOUNDATIONS OF THE CHINESE MODEL OF FUTURE MANAGEMENT - M. Yu. Zakharov (Вестник университета)
The article performs an analysis of the maxim of Ancient China, according to which further life, changes can be controlled if you first lift the veil of the past and present, look into the future and it is better to construct its desired image and move towards it. To this end, the author considers the traditional model of managing current changes and possible future, formed within the framework of the spiritual culture of China, which has found its modern embodiment in the technology of Chinese foresight. The paper determines the socio-cultural foundations of the model, the nature of prognostic knowledge, the features of its implementation in the form of effective inaction. The author pays special attention in the article to the understanding of the Chinese phenomenon of the future and its cosmological basis, the role of the “Supreme Ultimate” (Taiji) in the prognostic process, the latent side of the cognitive prognostic technology.